2003
DOI: 10.1183/09031936.03.00087902
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine production of RSV/PHA‐stimulated tonsillar mononuclear cells: influences of age and atopy

Abstract: Links between immune responses to respiratory syncytial virus (RSV), age and atopic sensitisation are poorly understood.This study investigated the induction of target organ type-1, type-2 and proinflammatory cytokine responses to RSV and/or phytohaemagglutinin (PHA) in tonsillar mononuclear cells from children, in relation to age and atopic status.In comparison with the control medium, RSV induced production of the type-1 cytokines interferon (IFN)-c and interleukin (IL)-18, the pro-inflammatory cytokines IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Ichinohe et al demonstrated that the capacity to produce IL-4 and IFN-γ in response to RSV infection increases with age 18. In our data, cytokine responses to initial RSV infection did not differ by age during infection.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Ichinohe et al demonstrated that the capacity to produce IL-4 and IFN-γ in response to RSV infection increases with age 18. In our data, cytokine responses to initial RSV infection did not differ by age during infection.…”
Section: Discussionsupporting
confidence: 61%
“…Studies have demonstrated the ability to produce IL-4 and IFN-γ cytokines increases with age in healthy infants 18, 21, 22. The evidence for IL-2 in healthy infants is less clear.…”
Section: Discussionmentioning
confidence: 99%
“…Whether RANTES level is also higher in the −403 A allele before one year of age and by recurrence of RSV is still the question needed to be solved in the future. Recent studies only indicated that RANTES was significantly increased in atopic children, which were dependent on RSV replication [10,17].…”
Section: Discussionmentioning
confidence: 99%
“…The result indicated that RANTES −403 A was responsible for elevated transcriptional activity in this work. Other factors such as the (−28 C/G) polymorphism [3] and infection disease [10,17] should not be ignored, which also contributed to the RANTES level. Polymorphism in IL-8 appears to determine the RSV bronchiolitis severity [9].…”
Section: Discussionmentioning
confidence: 99%
“…Recent interest has been focused on the associations of the host immune responses with disease severity [11]. Children exposed to RSV in early life or at a specific age tend to have a higher risk of severe lower respiratory infection [12], and this association was explained at least in part by the immature or impaired Th1 immune response in infancy [13,14]. In prospective studies, reduced interferon (IFN)-γ secretion from mitogen-stimulated cord blood cells has been linked to an increased number of moderate-to-severe viral respiratory infections [15].…”
Section: Introductionmentioning
confidence: 99%